Green Supply Chain Management Affects on Sustainability Of Energy Industry Participating in the Green Industry In Thailand - Singroengrit, Dusit; Jitnom, Saowaluk (Journal for Developing the Social and Community, 2026)
Background and Aims: Climate change and the critical need for reducing greenhouse gas emissions have driven the energy sector to adapt to environmental policies and sustainable development goals. This research aims to investigate the impact of Green Supply Chain Management (GSCM) on the sustainability of the energy industry participating in the Green Industry project in Thailand. Methodology: Using a quantitative approach, data were gathered through a questionnaire with an IOC range of 0.67-1.00 and Cronbach's alpha reliability coefficients between 0.892 and 0.914, distributed to 238 senior executives in certified Green Industry energy firms. Data were analyzed using descriptive statistics and Multiple Regression Analysis. Results: The findings reveal that most participating organizations are medium-to-large-scale petroleum blending businesses certified with ISO 14001, predominantly operating at Level 3 of the Green Industry certification (Green System). Hypothesis testing confirmed that GSCM practices collectively exert a significant positive influence on organizational sustainability (Sig.=0.000, p<.001), accounting for 19.4% of the variance in sustainable performance (R2adj = .194). Specifically, Green Operations emerged as the most significant predictor of sustainability with the highest effect size (𝛽 = .308, t = 4.612, p < .01), followed by Green Design (𝛽 = .153, t = 2.198, p < .05). Conversely, green purchasing, green manufacturing, and reverse logistics did not exhibit a statistically significant impact due to initial cost barriers and institutionalized baseline standards within the Thai context. Conclusion: These empirical results suggest that to achieve comprehensive long-term sustainability across economic, social, and environmental dimensions, energy firms must strategically prioritize the integration of green principles into their internal operational core and proactive product design processes.